The perspective and knowledge of Pejabat Pergigian Bahagian Kuching towards the implementation of total quality management / Aishah Latip - Latip, Aishah (2013)
Total Quality Management involves everything an organization, society, or a community does which in the eyes of others determines its reputation on a comparative basis with the best alternatives. The implementation of Total Quality Management in the public sector is a one of requirement from the government when the Development Administration Circular BI 1/1992 regarding to enhance total quality management n the public sector. This circular is intended to inform and guide the head of department the concept and development of total quality management. The study will examine the perspective and knowledge of Pejabat Pergigian Bahagian Kuching towards the implementation of total Quality Management The sample size for the purpose to this study involved of 40 employees which covering five {5) facilities in Pejabat Pergigian Bahagian Kuching in order to get the specific employees views. The perspective and knowledge of staff of implementation total quality management were examined. As a result, most employee understand the perspective and knowledge towards implementing Total Quality Management which reviews the several recommendation from upper management and low management to achieve a mutual cooperation in order to achieve the mission and vision of department.